For Ratio Analysis of the Efficiency of Budget Expenses on Social Policy Aimed at Overcoming Poverty in Russian Regions - M. L. Dorofeev (Вестник Российского экономического университета имени Г. В. Плеханова, 2023)
The development of methodology for analyzing efficiency is acute today due to fundamental basis of budget system functioning. The last ten years proved the importance of social policy and the welfare system during periods of uncertainty and economic crises. In 2022 the vector of Russian economy development changed from west to east and the country will face a long-term opposition through unprecedented sanctions and challenges to its economy transformation. The article puts forward a simple ratio method of analyzing efficiency of budget expenses aimed at overcoming poverty in Russian regions, systematizes the most frequently mentioned in academic literature methods of researching efficiency of expenses on social policy, investigates the method of analyzing the utmost efficiency and provides conclusions about its low practical significance. The article proposes to use the author’s approach to ratio analysis supplemented with ranking method, plotting heat maps and estimating basic descriptive statistics. Research findings demonstrate its high theoretic and practical value, especially as a preliminary stage of the research within the frames of a complex analytical approach to assessing efficiency of expenses on social policy allotted from consolidated budgets of Russian Federation entities.